Assessment of long-term psychosocial outcomes in N-methyl-D-aspartate receptor encephalitis – the SAPIENCE study protocol - Boeken, Ole Jonas; Heine, Josephine; Duda-Sikula, Marta; Patricio, Víctor; Picard, Géraldine; Buttard, Chloé; Benaiteau, Marie; Mendes, Álvaro; Howard, Fuchsia; Easton, Ava; Kurpas, Donata; Honnorat, Jérôme; et al. (BMC neurology, 2024)
Background N-methyl-D-aspartate-receptor (NMDAR) encephalitis is a rare neurological autoimmune disease with severe neuropsychiatric symptoms during the acute phase. Despite good functional neurological recovery, most patients continue to experience cognitive, psychiatric, psychological, and social impairments years after the acute phase. However, the precise nature and evolving patterns over time of these long-term consequences remain unclear, and their implications for the well-being and quality of life of predominantly young patients have yet to be thoroughly examined. Methods SAPIENCE is a European multi-center ( n = 3) prospective observational cohort study studying the long-term cognitive, psychiatric, psychological, and social outcome in patients with NMDAR encephalitis. The study consists of three interconnected levels. Level 1 comprises a qualitative interview and focus groups with patients and their caregivers. Level 2 consists of a condensed form of the interview, standardized questionnaires, and a detailed neuropsychological examination of patients. Level 3 involves an online survey that will be open to patients world-wide and explores patient-reported outcomes (PROMs), and patient-reported experiences (PREMs) in association with clinical and cognitive outcomes. Levels 1 to 3 will progressively contribute developing of structured interviews, survey questions, and treatment guidelines by informing one another. Discussion SAPIENCE is an in-depth study of the long-term effects of NMDAR encephalitis and bridges the gap between standardized assessments and individual patient experiences, intending to improve patient care and to increase awareness of the psychosocial long-term consequences of the disease. Through collaboration of experts in clinical neurology and social and health psychology across Europe, SAPIENCE aims to create online assessment tools and formulate guidelines for patient-centered post-acute care that will help enhance the quality of life for patients and caregivers.